2007
DOI: 10.1016/j.jtcvs.2007.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Necessary resection of the left lower lobe due to systemic arterial supply

Abstract: Symptomatic lung sequesters are usually treated with resection. 1 Most often the aberrant arterial supply is ligated or reimplanted onto the pulmonary artery. Baek and colleagues 2 recently described a patient with anomalous arterial supply of a left basal segment of the lung in which mere ligation of the anomalous artery produced a satisfactory result. 2 We present a similar case in which resection had to be performed despite our initial goal to preserve the entire lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Several studies have shown that the interlobar artery distal to the origin of the superior segmental artery is absent in ASALLL (10)(11)(12)(13)(14). In PS, however, normal pulmonary arteries are present in the left lower lobe (11,12). The absence of the interlobar artery distal to the origin of the superior segmental artery in the LLL may thus be a distinguishing feature of ASALLL (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the interlobar artery distal to the origin of the superior segmental artery is absent in ASALLL (10)(11)(12)(13)(14). In PS, however, normal pulmonary arteries are present in the left lower lobe (11,12). The absence of the interlobar artery distal to the origin of the superior segmental artery in the LLL may thus be a distinguishing feature of ASALLL (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the interlobar artery distal to the origin of the superior segmental artery is absent in ASALLL (10)(11)(12)(13)(14). In PS, however, normal pulmonary arteries are present in the left lower lobe (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are similar to previous reports. 4,5,9 Wu et al 10 reported ASALLL was related to Asian ethnicity, reporting that 47 (92%) of 51 cases in their study were of Asian ethnicity. The age range was from 6 months to 71 years, and the male-to-female ratio was 1.3:1.…”
Section: Discussionmentioning
confidence: 87%
“…3 Although lobectomy or segmentectomy can be performed in most cases of ASALLL and PS, other less invasive procedures, such as anastomosis between the anomalous artery and pulmonary artery, or embolization or ligation of the anomalous artery, can be performed in patients with ASALLL. 4,5 These procedures could shorten the hospitalization time. 4e6 Saida et al 6 reported that satisfactory clinical results were obtained in patients after 6 years of observation.…”
Section: Introductionmentioning
confidence: 99%